2008
DOI: 10.1103/physrevb.77.075316
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in PbSe nanocrystal arrays

Abstract: We report electrical transport measurements of arrays of PbSe nanocrystals forming the channels of field effect transistors. We measure the current in these devices as a function of source-drain voltage, gate voltage and temperature. Annealing is necessary to observe measurable current after which a simple model of hopping between intrinsic localized states describes the transport properties of the nanocrystal solid. We find that the majority carriers are holes, which are thermally released from acceptor state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
134
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 34 publications
7
134
2
Order By: Relevance
“…At the higher temperature range (160-300 K), the conductance fits well to an Arrhenius equation, ( ) = 0 − A B , with activation energy A . This observation agrees with previous studies on NC arrays of CdSe and PbSe, where simply activated or nearest neighbor hopping was found to be the dominant charge transport mechanisms at the 100-300 K temperature range [32,36]. In fitting our data, smaller error estimations were obtained in the 160-300 K than at the lower temperature range (Figure 5b inset).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…At the higher temperature range (160-300 K), the conductance fits well to an Arrhenius equation, ( ) = 0 − A B , with activation energy A . This observation agrees with previous studies on NC arrays of CdSe and PbSe, where simply activated or nearest neighbor hopping was found to be the dominant charge transport mechanisms at the 100-300 K temperature range [32,36]. In fitting our data, smaller error estimations were obtained in the 160-300 K than at the lower temperature range (Figure 5b inset).…”
supporting
confidence: 82%
“…This differentiates the effect from the Cu vacancy thermal-doping process mentioned above, which commences only at elevated temperatures (350-380 K [9]. To the best of our knowledge, such non-monotonic behavior was not observed in previous ( ) studies of NC arrays, where only a monotonic increase with temperature was found, conforming to some type of thermally activated transport [32,33]. We consider the origin of this behavior to be associated with a change in the density of states observed in Cu 2 S thin films at around 175 K. This transition is probably associated with a structural transition, as many of those are known for bulk Cu 2 S [34].…”
mentioning
confidence: 45%
“…After continuous illumination for 5 min at 100 mW cm −2 , the devices lost 70% of their initial power conversion efficiency, although they recovered within minutes of removal from light. This timescale indicates that decreased performance may result from inefficient electron extraction due to interfacial trapping 37 . The evaporation of a 1 nm layer of an electron extraction material, lithium fluoride 54 , between the nanocrystal layer and the aluminium electrode (Sup plementary Fig.…”
Section: Solar Cell Optimizationmentioning
confidence: 99%
“…In spite of this progress, there is a broad recognition of the need for innovations in materials. For instance, a narrower nanocrystal size distribution is expected to yield better performance owing to a greater uniformity of percolation networks 37 and a decrease in interstitial volume 38 .…”
mentioning
confidence: 99%
“…various theoretical models that predicted transport to occur through inefficient phononassisted (or 'hopping') conduction [6][7][8][9][10] or direct tunnelling, [2][3][4]11 leading to poor carrier mobility in these systems. Nevertheless surprisingly high mobilities were reported lately by several groups, [12][13][14][15][16][17][18] in high quality films made of different materials, suggesting that band-like transport through extended states is indeed achievable in CQD arrays, provided the surface traps are effectively passivated [18][19][20][21][22][23][24][25] and the separation between dots is reduced sufficiently by the use of extremely short ligands or inorganic capping.…”
mentioning
confidence: 99%